2019
DOI: 10.2174/2213809906666181214120504
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Entrepreneurial Intention in University Students of Mexico

Abstract: Background: Universities have shown to directly influence entrepreneurial activity in students [4-6], since they are concerned for the students to develop their entrepreneurial spirit [1-3], promoting Entrepreneurial Intention in University Students (EIUS). Objective: Therefore, the objective of this research is to determine a model of entrepreneurial intention of Mexican university students (EIUS), performing a multiple regression analysis, by the method of Ordinary Least Squares (OLS), on a sample of 538, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A state can thrive if the number of entrepreneurs is at least 2% of the total population. The results show that entrepreneurship education implementing a variety of modern methods has a significant impact on entrepreneurial attitudes and entrepreneurial intentions (Ríos-Manríquez et al, 2018). Entrepreneurial attitudes mediate the impact of entrepreneurship education on business intentions (Herta, 2019).…”
Section: The Effectiveness Of Case Studies In Entrepreneurship …mentioning
confidence: 97%
See 1 more Smart Citation
“…A state can thrive if the number of entrepreneurs is at least 2% of the total population. The results show that entrepreneurship education implementing a variety of modern methods has a significant impact on entrepreneurial attitudes and entrepreneurial intentions (Ríos-Manríquez et al, 2018). Entrepreneurial attitudes mediate the impact of entrepreneurship education on business intentions (Herta, 2019).…”
Section: The Effectiveness Of Case Studies In Entrepreneurship …mentioning
confidence: 97%
“…The Mexican researchers (Ríos-Manríquez et al, 2018) argue that universities have demonstrated a direct impact on student entrepreneurial activities by fostering entrepreneurial intentions of students as they want their graduates to develop the entrepreneurial potential.…”
Section: The Effectiveness Of Case Studies In Entrepreneurship …mentioning
confidence: 99%